Transfers to Region on Economic Growth During The Covid-19 Pandemic - Elsa Sari Yuliana; Ninik Kurniasih; Arianto Arianto; Mahyus Mahyus (Al-Makki Publisher, 2025)
The Covid-19 pandemic that began in late 2019 has had a significant impact on economies around the world, including Indonesia. In an effort to handle the pandemic, the Indonesian government has refocused the budget, one of which is through the transfer of funds to the regions. This study aims to analyze the effect of fund transfers to regions on economic growth during the Covid-19 pandemic in Indonesia. This research uses a quantitative approach with an exploratory case study method. The secondary data used includes local government financial reports and Gross Domestic Product (GDP) data from 34 provinces in Indonesia during 2020 to 2022. The analysis was conducted using statistical techniques with the help of SPSS. The results of the analysis show that the transfer of funds to the regions has a significant positive effect on economic growth, with an R-square value of 24.8%. However, 75.2% of economic growth is influenced by factors other than transfers. Fund transfer allocations that were originally intended to support regional development have been diverted to handling the impact of the pandemic. This study indicates that while financial transfers contribute to economic growth, there are many other factors that need to be considered. Therefore, further research is needed to understand the more complex dynamics in the effect of transfers on economic growth.